Univariate approach towards cocoa price forecasting - Mohd. Arshad, Fatimah; A. Ghaffar, Roslan (Malaysian Agricultural Economics Association, 1976)
A univariate ARIMA model methodology was utilised to forecast the short-run monthly price of dry cocoa beans. The appropriate model for forecasting was found to be (2, 1, 2) (1, 1, 1) 12. This model indicates that the original cocoa price series is non stationary and contains some elements of multiplicity; hence inheriting both autoregressive and moving average processes.